Numerical Analysis of Electro-Dynamic Stability Currents in Flexible Cables of Electrical Installations and Methods for Their Increase - I. I. Sergey; Y. G. Panamarenka (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2010)
The paper reveals design conditions while determining  electro-dynamic stability currents in flexible cables of electrical installations. The electro-dynamic stability currents of typical open-air 110–330 kV switching centers have been determined with the help of a  computing experiment. The paper contains justification in respect of methods for electro-dynamic stability increase of bus-bars by installation of inter-phase spacers and additional post insulators.